Disciplined agency : neoliberal precarity, generational dispossession and call centre labour in Portugal - Matos, Patrícia Alves de (New ethnographies., 2020)
This book introduces the concept of disciplined agency as a valuable explanatory tool vis-a-vis new forms of labour exploitation in service realms of production and the material and moral insecurities of capitalism under neoliberal governance.